2018
DOI: 10.1038/s41379-018-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological description of 43 oncocytic adrenocortical tumors: importance of Ki-67 in histoprognostic evaluation

Abstract: Oncocytic adrenocortical tumors are a rare subtype of adrenal tumors with challenging diagnosis and histoprognostic assessment. It is usually believed that oncocytic adrenocortical tumors have a more indolent clinical behavior than conventional adrenocortical tumors. As the Weiss score overestimates the malignancy of oncocytic adrenocortical tumors owing to intrinsic parameters, alternative scores have been proposed. The Lin-Weiss-Bisceglia score is currently recommended. We performed a large nationwide multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…One interesting subset includes five patients with oncocytic tumours. Oncocytic tumours, where at least 50% of the tumours comprise oncocytic cells, have been described as having more indolent courses compared to conventional ACC, with improved survival . This was confirmed in our cohort where Stage 2 oncocytic ACCs had equivalent survival to high Ki‐67 non‐oncocytic Stage 1 ACC.…”
Section: Discussionsupporting
confidence: 82%
“…One interesting subset includes five patients with oncocytic tumours. Oncocytic tumours, where at least 50% of the tumours comprise oncocytic cells, have been described as having more indolent courses compared to conventional ACC, with improved survival . This was confirmed in our cohort where Stage 2 oncocytic ACCs had equivalent survival to high Ki‐67 non‐oncocytic Stage 1 ACC.…”
Section: Discussionsupporting
confidence: 82%
“…However, it should be emphasised that the determination of the oncocytic character of the tumour cells represents another diagnostic hurdle. One of the reasons for this is that the determination of oncocytic character is based on subjective morphological criteria [2]. Our case was no exception, thereby requiring consultation with various pathologists.…”
Section: Discussionmentioning
confidence: 95%
“…Our case was no exception, thereby requiring consultation with various pathologists. Such diagnostic subjectivity is a major limitation to the use of a histoprognostic score [2]. Currently, AONs are classified based on the modified Weiss criteria, also known as the Lin-Weiss-Bisceglia (LWB) system, to elucidate their malignant potential [8], as this score does not include relatively more subjective histologic criteria, as in the original Weiss score [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present case, identification of 7 mitoses/50 HPFs and atypical mitoses definitively led to the diagnosis of oncocytic ACC. Renaudin et al reported 43 patients with oncocytic adrenocortical tumors in France and showed that both the Weiss criteria and the LWB criteria seemed to overestimate the potential malignancy of these tumors [16]. Further studies would be necessary to characterize the malignant potential of oncocytic tumors more accurately.…”
Section: Discussionmentioning
confidence: 99%